Penerapan Terapi Rendam Kaki Air Hangat untuk Mengurangi Kecemasan pada Ibu Hamil Pre Operasi Sectio Caesarea: Ruang Galdiol RSUD Dr. Tjitrowardojo Purworejo - Wulandari Wulandari; Despita Pramesti; Mulyanti Mulyanti (NAJ Nursing Applied Journal, 2025)
Anxiety is an emotional state characterized by feelings of discomfort, such as restlessness, worry, or fear of events that have not yet occurred. This condition is often experienced by pregnant women who are about to undergo labor, especially if confronted with an emergency cesarean section (CS). High anxiety can negatively impact the mother's physical and psychological condition, as well as affect the labor process. This study aims to determine the effectiveness of warm water foot soak therapy as a form of non-pharmacological intervention in reducing anxiety levels in pregnant women who will undergo cesarean section. This study used a case study design with a residential care approach. The study subjects consisted of two patients in the Gladiol Ward of Dr. Tjitrowardojo Purworejo Regional Hospital who experienced damage problems in the form of anxiety. The intervention provided was warm water foot soak therapy twice daily for two consecutive days. Data collection was carried out through interviews, observation, physical examinations, medical record studies, and filling out the Amsterdam Preoperative Anxiety and Information Scale (APAIS) questionnaire. The results showed that this therapy was able to reduce anxiety levels in both patients. The first patient showed a decrease from moderate anxiety (score 16) to mild anxiety (score 12), while the second patient experienced a decrease from severe anxiety (score 21) to moderate anxiety (score 17). Thus, warm foot soak therapy has been shown to be effective in reducing pre-CES anxiety and can be considered a safe and simple treatment intervention.